The research of net carbon reduction model for CCS-EOR projects and cases study. (2017) - Lu, Shijian; Liu, Hang; Zhao, Dongya; Zhu, Quanmin
This paper develops a calculation model of net carbon reduction for CCS-EOR, which is calculated by one minus the new generation CO2 by energy consumption during the processes of capture, transportation, injection and the recovery, meanwhile adding the re-injection CO2 content. By taking the CCS-EOR projects with the capacity of 0.5 million tons CO2 per year in the coal-fired power plant, coal chemical plant and chemical fertiliser plant as examples, we calculate the actual emission reductions and energy consumption per ton of CO2 with referencing to the current mainstream technology level. The results show that the net carbon reduction values in the two situations without and with recovery process of associated gas are respectively 0.4965 and 0.3951, 0.7624 and 0.6610, 0.7815 and 0.68 tons CO2, and the energy consumption values are 5.7405 and 6.6117, 2.7095 and 3.5807, 2.49185 and 3.36305 GJ in the three different plants.